A Drawing of Public Perception of Nurses' Caring Actions Based on Jean Watson's Carative Factor Theory at the Wolofeo Community Health Center, Ende District - Helena Kidi Labot; Maria Sofia Anita Aga; Maria Susana Ayufrida (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Caring is a fundamental concept in modern nursing practice that emphasizes empathy, presence, and therapeutic relationships between nurses and patients. As a core indicator of nursing care quality, caring behavior significantly influences patient satisfaction, comfort, and trust, particularly in primary healthcare settings. This study aimed to describe public perceptions of nurses’ caring practices based on Jean Watson’s Carative Factor theory at the Wolofeo Community Health Center (UPT). A descriptive quantitative design was employed involving 48 respondents selected through convenience sampling from a population of 93 individuals who had received nursing services. Data were collected using a modified Caring Assessment Tool (CAT) questionnaire based on Watson’s caring components and measured on a four-point Likert scale. The instrument demonstrated good validity and high reliability (Cronbach’s alpha = 0.87). Data were analyzed descriptively using frequency distributions and percentages. The results revealed that 93.75% of respondents perceived nurses’ caring behavior as good, while only 6.25% perceived it as poor. Most respondents were early adults, female, had a high school education, and worked as farmers or housewives, indicating that positive perceptions of caring extended across diverse demographic groups. These findings suggest that nurses at the Wolofeo Community Health Center have successfully implemented caring values, particularly in empathy, therapeutic communication, and creating a supportive care environment. In conclusion, caring practices aligned with Jean Watson’s theory contribute positively to patient experiences and trust in primary healthcare services. Strengthening caring through continuous training and humanistic service policies is recommended to sustain and enhance nursing care quality.